Study on particulate matter air pollution, source origin, and human health risk based of PM10 metal content in Volos City, Greece. Issue 4 (21st April 2017) - Emmanouil, Christina; Drositi, Eumorfia; Vasilatou, Vasiliki; Diapouli, Evangelia; Krikonis, Konstantinos; Eleftheriadis, Konstantinos; Kungolos, Athanasios
ABSTRACT: Investigations on the fluctuation in PM10 air pollution in Volos, a medium-sized industrialized port city in the Mediterranean, are presented for the 5-year period between 2009 and 2014. The levels detected have been examined in relation to legislatively set limits, sampling year, and day of the week. A PM10 spring sampling campaign has been performed in 2014 and metals and other elements in the PM10 mass have been quantified. Source origin has been attempted for the latter sampling campaign and human health risk has been assessed. Results show compliance with the mean annual value of 40 μg m −3 of 2008/50/EC for the city; however, exceedances of the daily quality standard of 50 μg m −3 were frequently recorded. Shifts in PM10 concentrations and in contributing sources have been recorded; nevertheless, longer duration data series are needed for safe deductions. Element measurements have enabled source identification for early summer of 2014, with Earth's crust minerals and anthropogenic sources being the main factors. Cumulative non-carcinogenic risk may exceed the threshold value of 1. Possible involvement of sea salt aerosol and desert dust long-range transport has also been assessed. These results may furnish databases on PM pollution of Greek cities as well as other Mediterranean urban centers with similar characteristics.